The rod pathway in the rabbit retina: a depolarizing bipolar and amacrine cell - Dacheux, RF (J Neurosci, 1986)
Anatomical and electrophysiological techniques were combined to study the morphology, synaptic connections, and response properties of two neurons in the rod pathway of the rabbit retina: the rod bipolar cell and the narrow-field, bistratified (NFB) amacrine cell. Rod bipolars receive synaptic input from rod cells in the outer plexiform layer (OPL), where their dendrites end as central elements in the invaginating synapse of rod spherules. Their main synaptic output in the inner plexiform layer (IPL) is onto NFB amacrine cells and at least one other type of amacrine, which in turn feeds a reciprocal synapse back onto the bipolar endings. Rod bipolars, or a variety of them, respond to diffuse, white light stimulation with a transient-sustained depolarization dominated by rods; with high-intensity flashes, they generate a secondary depolarization at off, which is homologous to the rod aftereffect of horizontal cells, although opposite in polarity. NFB amacrine cells receive synaptic input from rod bipolars, cone bipolars, and other types of amacrine cells; they are presynaptic to ganglion cell dendrites and communicate via gap junctions with other processes, whose parent neuron has not yet been identified. They respond to light with a triphasic potential, characterized by a depolarizing transient at on, followed by a sustained plateau phase, and finally by a hyperpolarizing transient at off. Threshold of their responses is the same as in the depolarizing rod bipolars and saturation is reached with nearly the same stimulus intensity in both neurons. Furthermore, NFB amacrine cells exhibit a depolarizing rod aftereffect at the termination of high-intensity flashes. Thus, this amacrine cell type is inserted in series along the rod pathway in the rabbit retina and modulates the transfer of scotopic signals from rod bipolars to ganglion cells.